2009
DOI: 10.1097/shk.0b013e318194bcee
|View full text |Cite
|
Sign up to set email alerts
|

TARGETED DELIVERY OF siRNA TO CELL DEATH PROTEINS IN SEPSIS

Abstract: Immune suppression is a major cause of morbidity and mortality in the septic patient. Apoptotic loss of immune effector cells such as CD4 T and B cells is a key component in the loss immune competence in sepsis. Inhibition of lymphocyte apoptosis has led to improved survival in animal models of sepsis. Using qRT-PCR of isolated splenic CD4 T and B cells, we determined that Bim and PUMA, two key cell death proteins, are markedly up-regulated during sepsis. Lymphocytes have been notoriously difficult to transfec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 45 publications
1
31
0
Order By: Relevance
“…FACS is also able to discriminate the expression of surface molecules from intracellular antigens: intracellular levels of TLR2 and TLR4 in NK cells from septic patients were increased compared to healthy subjects (79). Moreover, FACS allows the analysis of cell cycle phases and apoptosis, the programmed cell death mechanism known to play a key role in sepsis-associated tissue injury and immunoparalysis (84). …”
Section: Resultsmentioning
confidence: 99%
“…FACS is also able to discriminate the expression of surface molecules from intracellular antigens: intracellular levels of TLR2 and TLR4 in NK cells from septic patients were increased compared to healthy subjects (79). Moreover, FACS allows the analysis of cell cycle phases and apoptosis, the programmed cell death mechanism known to play a key role in sepsis-associated tissue injury and immunoparalysis (84). …”
Section: Resultsmentioning
confidence: 99%
“…Perhaps, if the comparisons were restricted to a particular cell class, such as circulating lymphocytes or monocytes, a much better correlation of the genomic response between mice and humans might have existed. In this regard, the dramatic upregulation in mouse lymphocytes of the genes encoding pro-apoptotic B cell lymphoma 2 (BCL-2) family members and downregulation of genes encoding anti-apoptotic BCL-2 family members has also been documented in lymphocytes from patients with sepsis 170,171 . The significance of this correlation for a particular class of genes in mice and humans is highlighted by the fact that apoptosis is a key pathogenic mechanism in sepsis.…”
Section: Figurementioning
confidence: 99%
“…Based on the observations that caspase-3, caspase-8 and caspase-9 molecules were activated, they concluded that both the extrinsic or death receptor apoptotic pathway (caspase-3 and caspase-8) as well as the mitochondrial apoptotic pathway (caspase-9) were involved in the lymphoid cell apoptotic process (20). Although lymphocyte caspase-3 activity was found to be increased, several preclinical trauma and sepsis studies did not find evidence to support a role for TNF or Fas ligand activation of the death receptor as the trigger which initiated the apoptotic response (21,22). Nonetheless, blockade of the extrinsic caspase-3 or the mitochondrial caspase-9 apoptotic pathways was effective in preventing sepsis or trauma-induced lymphoid tissue apoptosis (22).…”
Section: Discussionmentioning
confidence: 99%